2014
DOI: 10.1021/pr500556d
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Ebola Virus VP24 Cellular Interactome and Disruption of Virus Biology through Targeted Inhibition of Host-Cell Protein Function

Abstract: Viral pathogenesis in the infected cell is a balance between antiviral responses and subversion of host-cell processes. Many viral proteins specifically interact with host-cell proteins to promote virus biology. Understanding these interactions can lead to knowledge gains about infection and provide potential targets for antiviral therapy. One such virus is Ebola, which has profound consequences for human health and causes viral hemorrhagic fever where case fatality rates can approach 90%. The Ebola virus VP24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 30 publications
4
93
0
1
Order By: Relevance
“…Also, ebola virus (EV), which triggers severe hemorrhagic fever in humans with a high mortality rate, can be inhibited by cardiac glycosides. Na,K-ATPase was identified in a proteomic analysis of EV interaction with host cell proteins, and nanomolar concentrations of ouabain were able to impair the viral replication by decreasing the levels of viral RNA [24]. Additionally, this finding was confirmed by a screening of compounds with activity against EV [25].…”
Section: Rna Viruses Affected By Nak-atpase Modulationmentioning
confidence: 99%
“…Also, ebola virus (EV), which triggers severe hemorrhagic fever in humans with a high mortality rate, can be inhibited by cardiac glycosides. Na,K-ATPase was identified in a proteomic analysis of EV interaction with host cell proteins, and nanomolar concentrations of ouabain were able to impair the viral replication by decreasing the levels of viral RNA [24]. Additionally, this finding was confirmed by a screening of compounds with activity against EV [25].…”
Section: Rna Viruses Affected By Nak-atpase Modulationmentioning
confidence: 99%
“…2 Co-immunoprecipitated samples were then analysed using label free mass spectrometry. To investigate whether the interaction of NP with selected cellular proteins was mediated by RNA binding an RNAse treatment (15 units of RNAse (QIAGEN; 19101) was performed after the coimmunoprecipitations the with GFP-Trap.…”
Section: Np-egfp Co-immunoprecipitationmentioning
confidence: 99%
“…. 2 For western blot analysis the elution step was done in 100 l of 2xSDS-sample buffer (120mM Tris/Cl pH6.8; 20% glycerol; 4%SDS, 0.04% bromophenol blue; 10% -mercaptoethanol)…”
Section: Reverse Co-immunoprecipitationsmentioning
confidence: 99%
“…The interactome of PRRSV NSP12 was determined by high-affinity GFP pull-down coupled with label free mass spectrometry-based approach, which we have used previously to study virus/host protein interactions [16][17][18][19]. Our data identified112 cellular proteins probably interacted with NSP12, and these proteins were mainly nucleic acid binding proteins or chaperones and were grouped into several distinct functional clusters.…”
Section: Ifn-mediated Antiviral Responses In Order To Gain Time For Vmentioning
confidence: 94%
“…Third, 293T cells have already been successfully used in many studies to identify the cellular partners for different viral proteins [16][17][18][19]. Previous studies have reported that Marc-145 cells and PAMs behave quite differently in PRRSV infection [47].…”
Section: Accepted Manuscriptmentioning
confidence: 99%